Intermittent Caloric Restriction Promotes Erythroid Development and Ameliorates Phenylhydrazine-Induced Anemia in Mice - Bai, Meijuan; Cao, Peijuan; Lin, Yijun; Yu, Pengcheng; Song, Shuo; Chen, Lingling; Wang, Lan; Chen, Yan (Frontiers in Nutrition, 2022)
Background: Dietary restriction has a profound effect in altering immune system and promoting metabolic health and aging. However, how dietary restriction impacts erythroid system is largely unknown. We found that short-term caloric restriction (CR) stimulates expression of KLF1, a master regulator of erythroid development, in the spleen of mouse, and thus explored the potential effect of CR on hematopoiesis. Methods: We analyzed the effects of intermittent CR and continuous CR for different lengths of time on parameters of peripheral blood and erythroid profiles in the spleen and bone marrow in C57BL/6 mice. We next assessed how different types of CR affects phenylhydrazine-induced anemia in the mice. Colony formation assay was also used to analyze LK+ progenitors and BFU-e in the bone marrow. Results: Intermittent CR for 2 weeks raised the number of reticulocytes in the blood while continuous CR for 2 weeks elevated red blood cells and hemoglobin level. Intermittent CR for 2 weeks promotes extramedullary hematopoiesis in the spleen while continuous CR mainly promotes erythropoiesis in the bone marrow. Interestingly, short-term intermittent CR but not continuous CR is able to ameliorate phenylhydrazine-induced anemia. Intermittent CR reduces early-stage erythroblasts and increases late-stage erythroblasts/mature RBCs in the spleen, indicating an accelerated transition from early-stage to late-stage erythroblasts/mature red blood cells. Furthermore, short-term intermittent CR elevates LK+ progenitors and committed erythroid progenitor cells BFU-e in the bone marrow. Conclusions: Our study demonstrated that short-term intermittent CR, but not continuous CR, has a significant effect to promote hematopoiesis and such activity can ameliorate phenylhydrazine-induced acute anemia in the mouse.